The Influence of Injected Fluids on Microscopic Pore Structures in the Intersalt Dolomitic Shale Oil Reservoirs. (28th November 2019) - Zhou, Tong; Yan, Wei; Su, Jianzheng; Tang, Xianglu; Tian, Hao; Li, Wenbo; Wang, Kongyang; Sun, Ting; Wang, Ruyue; Zhang, Rusheng; Niu, Jun
Abstract : Given their low porosity and permeability, intersalt dolomitic shale oil reservoirs need to be developed via large-scale hydraulic fracturing to achieve economic effects. However, various lithologies and salt materials make these reservoirs vulnerable to salt mineral dissolution and recrystallization and salt plugging during development. This study investigated the variation rules of pore structures, porosity, and permeability of intersalt dolomitic shale oil reservoirs under the influence of hydraulic fracturing fluid. Correspondingly, a series of experiments (i.e., high-temperature and high-pressure soaking experiments, focused ion beam scanning helium ion microscope analyses, and porosity and pulse permeability tests) is performed on the Qian 3 4 -10 rhythmic intersalt dolomitic shales. Results show that distilled water dissolves the salt crystals inside the matrix pores to improve the reservoir permeability. However, the distilled water-rock interaction will cause the massive migration of salt minerals. By contrast, the supercritical CO2 can disperse salt particles, dredge the channels, and enlarge pores by expansion, but it has an overall weak capability of changing the pore structure and matrix permeability. To simulate the supercritical CO2 composite fracturing, the mixed solution of supercritical CO2 and distilled water favors the salt dissolution effect in the water-based fracturing fluid and recovery enhancement by CO2 . This solution can remarkably improve the reservoir porosity and permeability and avoid massive salt mineral migration and salt crystallization damage. This study is theoretically and practically important to the effective and enhanced development of intersalt dolomitic shale oil reservoirs.